Anaerobic digestion of poultry manure: Process optimization employing struvite precipitation and novel digestion technologies. Issue 1 (18th August 2016) - Farrow, Cameron; Crolla, Anna; Kinsley, Chris; McBean, Ed
Abstract : Solid‐state anaerobic digestion (SSAD) of poultry manure is assessed utilizing a combination anaerobic leaching bed (ALBR)/plug‐flow digester. Struvite precipitation is employed concurrently with digestion to control total ammoniacal nitrogen (TAN) and prevent inhibition of methanogenic archaea. Struvite precipitation reactions are performed at a pH of 7.0 to minimize microbiological stress when leachate is returned to the digester. Results demonstrate an increase in biogas yield of 30% (470 ‐ 607 L/kgVSin ) during batch digestion trials and up to 235% during semi‐continuous trials, when employing struvite precipitation methodologies. Methane content of the biogas is also shown to increase significantly ( P  < 0.05) when employing struvite precipitation. Of the three organic loading rates assessed (1.5, 3.0, 4.5 kg VS/m 3 day) during semi‐continuous digestion, 1.5 kg VS/m 3 day is shown to be the most efficient, with respect to biogas yield. © 2016 American Institute of Chemical Engineers Environ Prog, 36: 73–82, 2017